A COMPARISON BETWEEN EXPERIMENTAL AND NUMERICAL STUDIES FOR REINFORCED CONCRETE SLABS UNDER BLAST LOADING (GEOMATE Journal, 2022)
Explosion is a special load, it rarely happens, but consequences are very serious. Research on the effect of explosive loads on reinforced concrete (RC) slabs is important to reduce unexpected consequences. This research has been an interesting topic in Vietnam during recent years because there have been accidents due to explosive loads in the country. This is the basis for the design of military structures or special buildings in civil engineering in Vietnam. This paper presents experimental and numerical studies of the fracture response of RC slabs using materials available in Vietnam under blast loading. The concrete slabs with the length of 1000mm, the width of 800mm and the thickness of 120mm are manufactured and tested. The emulsion explosive has been used. Two cylindrical explosive blocks with masses of 0.5kg and 1.22kg are considered. These tests are modeled using the finite element method. Concrete is supposed to be brittle material and follow the Johnson–Holmquist-II (JH-2) model. The steel rebar is modeled following an elasto-plastic model. The emulsion explosive is converted to TNT explosive equivalent and modeled by the SPH method. The concrete crater, spall damage and dynamic behavior of concrete slabs under blast loading are considered. The comparison between experimental and numerical results allows to validate the numerical model to modeling the behavior of our concrete under blast loading.